2013
DOI: 10.1115/1.4025712
|View full text |Cite
|
Sign up to set email alerts
|

Type Curves Analysis for Asymmetrically Fractured Wells

Abstract: In this paper, a new constant rate solution for asymmetrically fractured wells was proposed to analyze the effect of fracture asymmetry on type curves. Calculative results showed that for a small wellbore storage coefficient or for the low fracture conductivity, the effect of fracture asymmetry on early flow was very strong. The existence of the fracture asymmetry would cause bigger pressure depletion and make the starting time of linear flow occur earlier. Then, new type curves were established for different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…Tiab et al (2010) discussed the influence of fracture asymmetry on the pressure behavior of a one-fracture well under constant production rate. Wang and Wang (2014) analyzed the effect of fracture asymmetry on type curves. They found that the fracture asymmetry has an important effect on fractured well productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Tiab et al (2010) discussed the influence of fracture asymmetry on the pressure behavior of a one-fracture well under constant production rate. Wang and Wang (2014) analyzed the effect of fracture asymmetry on type curves. They found that the fracture asymmetry has an important effect on fractured well productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Later, by considering the effect of the fluid flow within the hydraulic fractures, a seepage model of a vertical fractured well with two symmetrical finite-conductivity hydraulic fractures was established [20,21], which can identify the bilinear flow. Some researchers pointed out the existence of two asymmetrical hydraulic fractures in practice and established some seepage models of vertical fractured wells with two asymmetrical hydraulic fractures [22][23][24][25][26][27]. In fact, massive hydraulic fracturing usually creates fractured network or several main hydraulic fractures near the wellbore instead of two symmetrical/asymmetrical hydraulic fractures [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, general solutions considering the effects of dual-porosity effect in the reservoir was presented by Cinco-Ley and Meng 13 . The above solutions become the basic solutions of production data analysis 14 17 and some authors also considered fracture asymmetry based on the basic solutions 18 22 .…”
Section: Introductionmentioning
confidence: 99%